Microfluidic isolation of platelet-covered circulating tumor cells. Issue 20 (21st September 2017) - Jiang, Xiaocheng; Wong, Keith H. K.; Khankhel, Aimal H.; Zeinali, Mahnaz; Reategui, Eduardo; Phillips, Matthew J.; Luo, Xi; Aceto, Nicola; Fachin, Fabio; Hoang, Anh N.; Kim, Wooseok; Jensen, Annie E.; et al.
Abstract : A new CTC isolation approach uncovers special populations of platelet-coated CTCs and CTC-leukocyte clusters in cancer patients. Abstract : The interplay between platelets and tumor cells is known to play important roles in metastasis by enhancing tumor cell survival, tumor-vascular interactions, and escape from immune surveillance. However, platelet-covered circulating tumor cells (CTC) are extremely difficult to isolate due to masking or downregulation of surface epitopes. Here we describe a microfluidic platform that takes advantage of the satellite platelets on the surface of these "stealth" CTCs as a ubiquitous surface marker for isolation. Compared to conventional CTC enrichment techniques which rely on known surface markers expressed by tumor cells, platelet-targeted isolation is generally applicable to CTCs of both epithelial and mesenchymal phenotypes. Our approach first depletes unbound, free platelets by means of hydrodynamic size-based sorting, followed by immunoaffinity-based capture of platelet-covered CTCs using a herringbone micromixing device. This method enabled the reliable isolation of CTCs from 66% of lung and 60% of breast cancer (both epithelial) patient samples, as well as in 83% of melanoma (mesenchymal) samples. Interestingly, we observed special populations of CTCs that were extensively covered by platelets, as well as CTC–leukocyte clusters. Because these cloaked CTCs often escape conventional positive and negative isolation mechanisms, further characterization of these cells may uncover important yet overlooked biological information in blood-borne metastasis and cancer immunology.